2005
DOI: 10.1258/004947505774938666
|View full text |Cite
|
Sign up to set email alerts
|

Deaths associated with anaesthesia in Togo, West Africa

Abstract: This study attempts to determine the anaesthetic death rate, the causes of deaths and the avoidable mortality rate (AMR) in consecutive cases. The number of anaesthetics given was 1464: 30 cases died within 24 h. The incidence of 24-h perioperative deaths per 100 anaesthetics was 2.57. In all, 50% of deaths were observed in obstetric surgery; 47% of deaths were associated with cardiovascular management, 30% with respiratory management; 93% of deaths were identified as avoidable. The AMR was 1.5% (anaesthetic A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
96
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 5 publications
1
96
1
3
Order By: Relevance
“…Very high perioperative mortality rates have been reported for adults and children in hospitals in lowincome countries, where many avoidable deaths have been associated with failures in administrative procedures, anaesthesia and surgical care. [32][33][34][35][36][37] These studies have included deaths on the wards up to 6 days postoperatively and have shown perioperative mortality rates of 26 to 257 deaths per 10 000 operations, as well as anaesthesia complications frequently related to failures in airway management (including tracheal intubation), respiratory monitoring and in reversing paralysis after anaesthesia. [33][34][35][36][37] Children who undergo surgery in Uganda are frequently given ketamine, an effective and safe anaesthetic and analgesic agent, and since ketamine generally preserves airway patency, it is often used without tracheal intubation or paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Very high perioperative mortality rates have been reported for adults and children in hospitals in lowincome countries, where many avoidable deaths have been associated with failures in administrative procedures, anaesthesia and surgical care. [32][33][34][35][36][37] These studies have included deaths on the wards up to 6 days postoperatively and have shown perioperative mortality rates of 26 to 257 deaths per 10 000 operations, as well as anaesthesia complications frequently related to failures in airway management (including tracheal intubation), respiratory monitoring and in reversing paralysis after anaesthesia. [33][34][35][36][37] Children who undergo surgery in Uganda are frequently given ketamine, an effective and safe anaesthetic and analgesic agent, and since ketamine generally preserves airway patency, it is often used without tracheal intubation or paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to staffing, it is no coincidence that the available numbers of labor midwives and nurse anesthetists were correlated with improvement, because both provide important lifesaving functions [14][15][16][17]. The worsening staffing ratios for many provider groups in this report are concerning.…”
Section: Discussionmentioning
confidence: 73%
“…[20][21][22] Education for mothers, caregivers, and nurses was nearly always able to lower the MFT. Different methods were used during the 5-year study.…”
Section: Discussionmentioning
confidence: 99%